Politics and International Criminal Court Debate: A Critical Discourse Analysis of Utterances by Politicians in Kenya - Jagero, Juliet Akinyi (Richtmann Publishing, 2012)
Language plays a critical role in political action. The choice of words written or spoken is a very important tool inpolitical engagements. This paper aims at analyzing utterances by politicians in Kenya on International Criminal Court (ICC)debate. This study uses Critical Discourse Analysis (CDA) to analyze these utterances so as to reveal the sources of powerabuse, dominance, inequality and bias and how these sources are initiated, maintained, reproduced and transformed withinspecific political and historical context. This paper draws data from political speeches and utterances from press conferences,Newspapers, interviews, political rallies and other forms of media from the time the ICC debate begun in the year 2009 afterparliament voted against constitutional amendment that would have allowed a credible and independent local court. From theanalysis it is evident that politicians use language that does not conform to the norms of the society and thus threatening nationalcohesion and perpetuating animosity among different ethnic groups as they politicize the ICC debate.